Motivation of Woman Shopping in Traditional Market in Surabaya City - Sarie, Rena Febrita (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
This research is about the shopping behavior of woman in traditional market. The result of the study that there are motivations shopping in traditional market in Surabaya. This research uses qualitative approach. This sample of study was 20 people, with the criteria ten women were working woman and ten others were housewives by using snowball sampling technique. There are 12 themes emerge in this study namely shopping motivations are Many sellers, Cheaper price, Many choices, Good quality products, The price can be negotiable, More Economized, If consumer want the need in high quantity, If there aren’t goods in vegetable mobile seller either in modern market, If consumer has no time to buy the need in mobile vegetable seller, completeness, the product can be sold in small quantity, If the vegetable mobile sellers do not sell. The most motivated motivation by consumers shopping in traditional market is they can get cheaper price The government should make a fair regulation among traditional market and modern retail.